Investigating energy storage ability of MIL101-(Fe) derivatives prepared using successive carbonization and oxidation for supercapacitors. (1st November 2022) - Wu, Yung-Fu; Kuo, Tsung-Rong; Lin, Lu-Yin; Kubendhiran, Subbiramaniyan; Lai, Kuan-Chen; Chen, Tzu-Yang; Yougbaré, Sibidou
Abstract: Metal organic framework (MOF) with high surface area and tunable porous size is largely used as active material of supercapacitor (SC). MIL-101(Fe) composed of iron ions and terephthalic acid ligand is candidate active material of SC owing to its possible formation of carbon and iron compounds. Combining carbon and metal compound is feasible to establish efficient active material with ion adsorption/desorption and redox reaction charge storage abilities. In this study, it is the first time to investigate physical and electrochemical properties of MIL101(Fe) derivatives synthesized using carbonization and successive carbonization/oxidation processes as active materials of SC. Carbonization temperature of MIL-101(Fe) is optimized regarding to morphology, composition and defect/graphization ratio. The highest specific capacitance (CF ) of 95.7 F/g at 20 mV/s is obtained for the carbonized MIL-101(Fe) (MIL101(Fe)-C) prepared at 800 °C, due to rough surface, hollow structure and suitable defect to graphization ratio. The MIL-101(Fe) and the successive carbonization/oxidation synthesized derivative electrodes merely achieve CF values of 44.3 and 0.1 F/g, respectively. Symmetric SC fabricated using optimized MIL101(Fe)-C electrodes shows the maximum energy density of 1.13 Wh/kg at 400 W/kg and excellent cycling stability with CF retention of 96% and Columbic efficiency of 72% in 8000 times repeated charging/discharging cycles. Graphical abstract: Unlabelled Image Highlights: MIL101(Fe) derivative was made in carbonization and carbonization/oxidation ways. The MIL-101(Fe) carbonized at 800 °C shows a specific capacitance (CF ) of 95.7 F/g. Due to rough surface, hollow structure and suitable defect to graphization ratio Symmetric supercapacitor shows maximum energy density of 1.13 Wh/kg at 400 W/kg. The CF retention of 96 % and Coulombic efficiency of 72 % were got after 8000 cycle.